Realizing large-scale and controllable fabrication of active cobalt oxide nanorod catalysts for zinc-air battery. (2nd February 2019) - Da, Pengfei; Wu, Mengying; Qiu, Kangwen; Yan, Dongyang; Li, Yuejiao; Mao, Jing; Dong, Cunku; Ling, Tao; Qiao, Shizhang
Graphical abstract: Highlights: We realize the controllable and large-scale fabrication of CoO nanorods directly on CFP. The CoO nanorods based Zn-air battery achieves higher performance than Pt/C and RuO2 . The CoO nanorods are easily assembled into all-solid-state Zn-air battery. Abstract: Driven by the intensified demand for energy storage systems with high-energy density and safety, all-solid-state zinc (Zn) air batteries have drawn extensive attentions. However, the development of non-precious metals with high catalytic activity as the air electrode is still a big challenge. In this work, we realize the large-scale fabrication of single-crystal CoO nanorods with high active facets and abundant oxygen vacancies in-situ on conductive substrate, which exhibits superior electrocatalytic activity in both oxygen reduction reaction and oxygen evolution reaction. The all-solid-state Zn-air batteries assembled with such free-standing CoO NRs show low charge/discharge overpotentials, a high energy density and a high cyclic stability. Our work indicates that the rational structure design of catalysts can pave a new route to next generation efficient and durable electrochemical devices.